Description of the Last Instar Larva of Phyllocycla gladiata (Hagen in Selys) (Anisoptera: Gomphidae) - Carriço, Cesar (2011)
The larva of the last instar of Phyllocycla gladiata (Hagen in Selys) is described and illustrated based in only one exuviae, collected at Camorim River, Jacarepaguá, Rio de Janeiro State, Brazil. Exuviae is deposited in the Museu Nacional (UFRJ), Rio de Janeiro, Brazil. Descrição do Último Ínstar Larvar de Phyllocycla gladiata (Hagen in Selys) (Anisoptera: Gomphidae) Resumo. A larva do último ínstar de Phyllocycla gladiata (Hagen in Selys) é descrita e ilustrada com base em uma exúvia coletada no Rio Camorim, Jacarepaguá, Rio de Janeiro, Brasil. A exúvia foi depositada no Museu Nacional (UFRJ), Rio de Janeiro, Brasil.